HUMAN RESOURCE MANAGEMENT PRACTICES AND THEIR OUTCOMES IN SRI LANKAN PUBLIC SECTOR BANKS - Mangaleswaran, T.; Srinivasan, P.T. (University of Sri Jayawardenepura, 2008)
This research focuses on Human Resource Management Practices (HRMP) and their outcomes in Sri Lankan Public Sector Banks. HRMP have been studied extensively among manufacturing, service and small medium enterprises. However, only a few studies have addressed the banking industry. Surprisingly, the research studies of this nature have rarely been conducted to assess HRMP and their outcomes such as Job Satisfaction and Organizational Commitment in banking environment. Through the survey method by the use of a structured questionnaire designed to test employee’s perceptions, the data were collected. A sample of 281 employees from two Sri Lankan Public Sector Banks was used. Confirmatory factor analysis, Cronbach alpha, Stepwise Multiple Regression and Structural equation model (Path analysis) were used for various analyses of this study. HRMP are significant predictors of Job Satisfaction and Organizational Commitment; Job Satisfaction dimensions also significantly predict Organizational Commitment; HRMP lead to Job Satisfaction and Organizational Commitment.
Keywords: Human Resource Management; Job Satisfaction; Organizational Commitment